Organization - Warner, Malcolm (Henry Stewart Talks, 2010)
Ubiquity of organizations, Defining organizations, Organizational rationales, Organizational structure, The 'shadow-side' of organizations, Hybrid organizations, Network-based organizations, Self-managed teams, Virtual organizations, Challenges, Conclusions, Readings